Effectiveness of PjBL-STEM Based Edukit Biocomposter Learning Media on Environmental Pollution Materials to Train the Creativity of VII Grade Junior High School Students - Hamimi, Erti; Diastuti, Adinda Hanif (Unnes Science Education Journal, 2024)
21st century education requires students to develop thinking skills, one of which is creative thinking. One learning model that can be used to train creative thinking skills is PjBL-STEM with educational media. This research aims to measure the effectiveness of the biocomposter edukit PjBL-STEM based in training students creativity in environmental pollution material. The development model used is quantitative research method which displays details of data collection and analysis to measure the effectiveness of edukit in improving creativity skill. Quantitative data were obtained from media and material validation, teacher and student practicality tests, as well as limited effectiveness tests using the result scores from the pretest and posttest questions. While qualitative data obtained from teacher interviews. Data collection techniques using interviews, questionnaires, and questions. Data analysis techniques were carried out using descriptive qualitative and percentage analysis. The pretest and posttest results in this study showed a difference,  the pretest data with a significance value of 0.219 and the posttest data with a significance value of 0.138. Based on the results of expert validation, practicality tests, and limited effectiveness tests, it can be concluded that the PjBL-STEM based biocomposter is very feasible, practical, and effective for use in class VII environmental pollution materials to train creative thinking skills.